Anti-proliferative and Chemotherapeutics Effects of Nigerian Honey and Its Polyphenols on Cancer cells - Ahmad, Umar Salisu; Buhari, Ibrahim; Umar, Aminu Kura; Usman, Pateh Umar (My University, 2020)
Cancer is one of the major deadly diseases affecting humans around the world, Nigeria inclusive. Liver cancer also known as hepatocellular carcinoma (HCC) is the fifth most common cancer in males and the seventh most common cancer in females and the third leading cause of cancer death globally [1]. Limited treatment for high-risk liver cancer and poor prognosis was recorded, in addition to its resistance, recurrence, progression and invasion. Resistance of liver cancer to conventional therapies added to severe side effects prompted the search for a novel therapeutic approach based on natural products such as the Nigerian honey. Honey and its components were documented to have significant anti-cancer activity against many types of cancer including liver cancer in both in vivo and in vitro studies. However, the mechanism of anti-cancer activity of honey as a chemopreventive and therapeutic agent has not been completely elucidated, and to our knowledge, there is no study carried out to investigate the effects of Nigerian honey on cancer cells. It is in view of this that this project aims to pre-clinically evaluate the molecular mechanism of anti-cancer activity of the Nigerian honey on liver cancer cells through the use of molecular techniques. A full understanding of cellular and molecular mechanisms elicit by honey in killing cancer cells may lead to the use of the honey or its polyphenols at clinical level for effective treatment of many types of human cancer in the future.
Keywords: Cancer; Anti-proliferation; Chemotherapeutics